Employment Rate Gaps between Immigrants and Non-immigrants in Canada in the Last Three Decades - Lu, Hao (Université d'Ottawa | University of Ottawa, 2015)
This study uses six Canadian censuses spanning from 1981 to 2006 and the 2011 National Household Survey to examine employment rate gaps between immigrants and non-immigrants during thirty years. Recent immigrants are found to have lower probabilities of being employed than Canadian-born people. The employment rate gaps of immigrants are analyzed through the estimations of entry, assimilation and cohort effects. The entry effect is the estimated immigrants’ employment penalty at the year of arrival; the assimilation effect refers to the difference in the returns to experience between immigrants and natives; and the cohort effect represents immigrants’ “quality” change through different arriving cohorts. The paper identifies some of the reasons leading to a worsened labour market performance of recent immigrants. Entry effects and cohort effects can be explained by the shift in the composition of new immigrants and by the macroeconomic conditions. The speed of assimilation effect can be related to the distribution of educational achievements of recent immigrants and to the concentration of places of residence.